The dynamics of FLOWERING LOCUS T expression encodes long-day information - Krzymuski, Martin Javier (2015)
Long days repeatedly enhance the expression of the FLOWERING LOCUS T (FT) gene during the evening and early night. This signal induces flowering despite low FT expression the rest of the day. To investigate whether this temporal behaviour transmits information, plants of Arabidopsis thaliana were exposed to different day–night cycles, including combinations that induced FT expression out of normal hours. Flowering time best correlated with the integral of FT expression over several days, corrected for a higher evening and early night sensitivity to FT. We generated a system to induce FT expression in a leaf removed 8–12 h later. The expression of flowering genes in the apex and flowering required cycles of induction repeated over several days. Evening and early night FT induction was the most effective. The temporal pattern of FT expression encodes information that discriminates long days from other inputs.